Atherosclerosis as a problem in postmenopausal women - Agnieszka Nawrocka; Paweł Mlicki; Karolina Matulewicz; Bogusz Olszewski; Jakub Dorobiała; Aleksandra Wyszyńska; Aleksandra Wijata; Marianna Kur; Zuzanna Leśniak; Marta Lewandowska; Jakub Husejko; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2019)
Introduction: Atherosclerosis is defined as a disease in which plaque, consisting of fat, cholesterol and other substances found in blood, builds up in arteries. This leads to stiffness and narrowing of the blood vessels resulting in limiting the flow of the blood rich in oxygen to tissues. The negative effect of atherosclerosis among women can be opposed by the female hormones. The aim of the article is to review clinical approach to atherosclerosis in post-menopausal women. Material and methods: Articles in the Google Scholar, Pub Med database have been analysed using keywords: atherosclerosis, plaque, cardiovascular diseases, menopause, postmenopausal women, female hormones, estrogens, older people. Results: Atherosclerosis process in the arterial walls is based on accumulation of lipids accompanied by inflammatory factors. One of the most important risk factors of this disease are quantitative and qualitative changes of the plasma lipoprotein, especially increasement of LDL cholesterol after menopause, which can be evaluated during lab tests. The diagnosis of atherosclerosis and its progress can be performed by using different methods, including physical examination and medical imaging. Development of atherosclerosis leads to peripheral artery disease connected with cardiovascular diseases, such as stroke or heart attack, which be life-threatening and should be immediately treated. Conclusions: This risk of the negative effects of atherosclerosis can be decreased by both lifestyle change and pharmacological treatment. The usage of estrogen-based hormone replacement therapy combined with statins in postmenopausal women presents benefits by the decreasement of LDL cholesterol and the increasement of HDL cholesterol and reduction of calcification of coronary vessels, which reduces the risk of cardiovascular diseases. However, the time of the start of hormone replacement therapy is crucial - performed too late can result in additional development of atherosclerotic plaque and increasement of the inflammatory processes in the arteries with advanced atherosclerotic changes.